Grief & Loss Resolution among Birth Mothers in Open Adoption - Krahn, Lisa; Sullivan, Richard (Canadian Social Work Review / Revue canadienne de service social, 2015)
While research has explored birth parent grief and loss, it has not been thorough in exploring how the experience of having an open adoption affects birth parents’ grief and loss experience and resolution. Previous research has highlighted positive effects of open adoptions to date, but is quite limited in regards to the birth parents’ adjustment in current day, open adoptions. This descriptive, qualitative study explores birth parents’ experiences in current day, open adoptions and seeks to understand their experience of grief and loss and their movement towards grief resolution in the context of an open adoption. Findings of this study confirm that the experience of adoption placement involves grief and loss and that openness in adoption helps to mitigate this painful experience. Most notably, birth parents found meaning, comfort, and peace in knowing of their child’s well-being and by having ongoing involvement in the life of the child and adoptive family. This opens new avenues in thinking about adoption and the meanings participants make of it.